Inflammatory bowel disease and the South Asian diaspora. Issue 5 (22nd February 2019) - Farrukh, Affifa; Mayberry, John Francis
Abstract : Migration is associated with changes in the incidence of diseases, often linked to new environmental exposures or movement away from such exposures. Studies are complicated by the time and length of migration and also by differences in the experience of second‐ and third‐generation migrants. South Asian people have migrated across the world. In this review, the incidence and prevalence of inflammatory bowel disease in these communities is considered, along with their potential role in future investigative studies of the diseases' etiology. Abstract : Inflammatory bowel disease occurs with a similar frequency to the host nation in South Asian migrants. The existence of family networks across the world opens up the prospects of new forms of study into the etiology of inflammatory bowel disease.